Prevalence of reduced carbon monoxide transfer factor in smokers with normal spirometry. (June 2021) - Cheung, Timothy; Papanikolaou, Vicki; Finlay, Paul; Yong, Theresa; MacDonald, Martin; Thompson, Bruce R.; Bardin, Philip G.; King, Paul T.
Abstract: We report the prevalence of reduced levels of carbon monoxide transfer factor (TLCO) in middle-aged current or ex-smokers with normal spirometry. Spirometry and TLCO measurements were performed and we identified 391 subjects aged 40–60 years, with a significant smoking history and normal spirometry. In this group, 96 subjects (24%) had TLCO measuremements below the lower limit of normal when using the newly established Global Lung Initiative (GLI) reference equations. The measurement of TLCO should be considered as part of the standard assessment of smokers. Highlights: A reduced carbon monoxide transfer factor is a prevalent finding in smokers with normal spirometry. Results differ when different reference equations are used. A low TLCO in these subjects may be an important, early marker of lung pathology.